POLICY STRATEGY TO MANAGE SUSTAINABILITY OF SITU (SMALL LAKE) KEDAUNG IN PAMULANG DISTRICT, SOUTH TANGERANG, BANTEN-INDONESIA - Agus Susanto (Departement of Agribusiness Faculty of Science and Technology, 2018)
South Tangerang City Government set it Situ (small lake) Kedaung as one of the conservation program, because of 9 there were 4 of which have been lost or switching functions, and 3 endangered missing, one of them is Situ Kedaung. For it is necessary to study the level of sustainable conservation to utilization Situ Kedaung. This study aims to analyze the index and status sustainability of 5 (five) dimensions of sustainability, using the data step Multi-Dimensional Scaling (MDS), and the results are expressed in the form of index and status of sustainability. To determine the attributes that are sensitive and affect the index and status sustainability and influence of Laverage and Montecarlo analysis. As for the scenarios increase the sustainability of the future status is a prospective analysis. The analysis showed that the ecological dimensions of sustainability are at less status (37.32), the economic dimension is the less sustainable status (26.05), the social dimension is the less sustainable status (40.28), the dimensions of the technology is fair sustainable status (57.20), and institutional dimensions are less sustainable (26.91). The results of the analysis of all the dimensions of sustainability for situ Kedaung is included in the category or status less sustainable with index value of 36.65. Of the 37 attributes that were analyzed, there were 14 attributes that need to be addressed as it is sensitive affect. Based on a prospective analysis, there are 5 critical attributes that must be managed in order to maintain sustainability. These five attributes include: water pollution, eco-tourism, conservation, community income, and local regulatory agencies, hereinafter referred to as key attributes. To improve the status of sustainability in the future (over the medium and long term), there are three scenarios : (1) Conservative-Pessimistic (survive the conditions that exist while holding make shift repairs), (2) moderate- Optimistic (make improvements but not optimal) and (3) Progressive- Optimistic (make comprehensive and integrated improvements).